A Protein Antagonist of Activation-Induced Cytidine Deaminase Encoded by a Complex Mouse Retrovirus - Gurvani B. Singh (American Society for Microbiology, 2019)
ABSTRACT Complex human-pathogenic retroviruses cause high morbidity and mortality worldwide, but resist antiviral drugs and vaccine development due to evasion of the immune response. A complex retrovirus, mouse mammary tumor virus (MMTV), requires replication in B and T lymphocytes for mammary gland transmission and is antagonized by the innate immune restriction factor murine Apobec3 (mA3). To determine whether the regulatory/accessory protein Rem affects innate responses to MMTV, a splice-donor mutant (MMTV-SD) lacking Rem expression was injected into BALB/c mice. Mammary tumors induced by MMTV-SD had a lower proviral load, lower incidence, and longer latency than mammary tumors induced by wild-type MMTV (MMTV-WT). MMTV-SD proviruses had many G-to-A mutations on the proviral plus strand, but also C-to-T transitions within WRC motifs. Similarly, a lymphomagenic MMTV variant lacking Rem expression showed decreased proviral loads and increased WRC motif mutations relative to those in wild-type-virus-induced tumors, consistent with activation-induced cytidine deaminase (AID) mutagenesis in lymphoid cells. These mutations are typical of the Apobec family member AID, a B-cell-specific mutagenic protein involved in antibody variable region hypermutation. In contrast, mutations in WRC motifs and proviral loads were similar in MMTV-WT and MMTV-SD proviruses from tumors in AID-insufficient mice. AID was not packaged in MMTV virions. Rem coexpression in transfection experiments led to AID proteasomal degradation. Our data suggest that rem specifies a human immunodeficiency virus type 1 (HIV-1) Vif-like protein that inhibits AID and antagonizes innate immunity during MMTV replication in lymphocytes. IMPORTANCE Complex retroviruses, such as human immunodeficiency virus type 1 (HIV-1), cause many human deaths. These retroviruses produce lifelong infections through viral proteins that interfere with host immunity. The complex retrovirus mouse mammary tumor virus (MMTV) allows for studies of host-pathogen interactions not possible in humans. A mutation preventing expression of the MMTV Rem protein in two different MMTV strains decreased proviral loads in tumors and increased viral genome mutations typical of an evolutionarily ancient enzyme, AID. Although the presence of AID generally improves antibody-based immunity, it may contribute to human cancer progression. We observed that coexpression of MMTV Rem and AID led to AID destruction. Our results suggest that Rem is the first known protein inhibitor of AID and that further experiments could lead to new disease treatments.